Quantifying Anharmonic Vibrations in Thermoelectric Layered Cobaltites and Their Role in Suppressing Thermal Conductivity - Fujii, Susumu (Sci Rep, 2018)
Optimizing multiple materials properties which are simultaneously in competition with each other is one of the chief challenges in thermoelectric materials research. Introducing greater anharmonicity to vibrational modes is one strategy for suppressing phonon thermal transport in crystalline oxides without detrimentally affecting electronic conductivity, so that the overall thermoelectric efficiency can be improved. Based on perturbed molecular dynamics and associated numerical analyses, we show that CoO(2) layers in layered cobaltite thermoelectrics Na(x)CoO(2) and Ca(3)Co(4)O(9) are responsible for most of the in-plane heat transport in these materials, and that the non-conducting intermediate layers in the two materials exhibit different kinds of anharmonicity. More importantly, thermal conduction is shown to be altered by modifying the structure of the intermediate layers. The simulation methods developed to quantify the effect of anharmonic atomic vibrations on thermal conductivity provide a new tool for the rational design of thermoelectric materials, and the insights gained should hasten the attainment of higher conversion efficiencies so that thermoelectrics can be put to widespread practical use.